Management of vision loss associated with complications of cosmetic filler injections - Madala, Samantha; Davuluru, Shaili; Li, Joy; Gluckstein, Jeffrey; Martin, John; Khatibi, Kasra; Zhang-Nunes, Sandy (Frontiers in Ophthalmology, 2025)
Injectable cosmetic fillers have dramatically risen in popularity in recent years. However, as the use of such fillers has become more common, there have been many reports of vision loss secondary to misplaced filler embolizing to the ophthalmic artery resulting in ocular ischemia. Currently, there are no randomized control trials or widely validated clinical guidelines that dictate how injectors should manage ischemic complications of filler embolism. This review aims to explain the possible mechanisms by which a cosmetic filler embolus can occlude the ophthalmic artery, describe the types of treatments that have been attempted thus far, and delineate possible a stroke-like protocol that can be implemented in order to restore perfusion and recover vision after such ischemic complications have occurred.